La prevención y sanción proporcional a los responsables del acoso escolar (bullying) en los establecimientos educativos, a cargo de la junta de protección de derechos de la niñez y adolescencia - Briceño Torres, Samuel Olivo (2014)
The present investigative work of thesis of Grade of Lawyer, takes for title: "The prevention and proportional sanction to those responsible for the school pursuit (bullying) in the educational establishments, in charge of the meeting of protection of rights of the childhood and adolescence", it is product of the study carried out to the current reality for that you/they come crossing the children, girls and adolescence in the educational centers that are mistreated, humiliated by other partners, without the authorities of the establishment and competent public authorities of the protection of the rights of the one smaller than age, they have not made anything to eradicate this abuse type that injures the victim's personal integrity. So lamentable it is to listen cases in that the children or adolescents suffer since rather of depression, anxiety and other situations that should not be affecting them in that stage of the life, it is when more it is enjoyed happiness and almost one neither it is given for informed that problems exist in the schools or public or private schools. The Code of the Childhood and Adolescence preceptúa the rights that you/they enjoy those smaller than age and that they are guaranteed in the Constitution of the Republic of the Ecuador, and protected by the National System of Protection of the Rights of the Childhood and Adolescence; that it stops their application it has created organisms that worry in making them complete. Among a protection organisms we find the Cantonal Meeting of protection of Rights of the Childhood and Adolescence; with competitions to dictate measured sancionadoras to those responsible for abuses to those smaller than age, inclusive in the centers or educational establishment, and their offenders receive proportionate sanctions that are ejemplarizadoras, and be good for the criminal prevention, sanctions should also be applied with obligatoriedad to the responsible ones and to offer services like psychological treatment to the parts. The theoretical, juridical and doctrinal storing, the study of concrete cases, the application of surveys and interviews, he/she allowed to obtain approaches with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of the objectives and the contrastación from the relating outlined hypotheses to this practice; as much the Constitution as the other laws that protect to those smaller than age, and the international instruments of direct and immediate application in the event of vulneración, what bears an itemized study of the execution of the rights of the children and adolescents to belong to a group of high-priority attention.